2014
DOI: 10.1186/1471-2261-14-97
|View full text |Cite
|
Sign up to set email alerts
|

Using the LACE index to predict hospital readmissions in congestive heart failure patients

Abstract: BackgroundThe LACE index has been used to predict the risk of unplanned readmission within 30 days after hospital discharge in both medical and surgical patients. The aim of this study is to validate the accuracy of using the LACE index in CHF patients.MethodsThis was a retrospective study. The LACE index score was calculated on each patient who was admitted to hospital due to an acute CHF exacerbation. Operational and clinical variables were collected from patients including basic clinical characteristics, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
76
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 27 publications
7
76
0
2
Order By: Relevance
“…Although recent research [14] concludes that LACE (which is the base for LACE+) could not accurate predict unplanned readmission, the presented system will include more data than LACE. One of the reasons is that in the available data there can be found a set of variables different from the ones used in LACE+ validation.…”
mentioning
confidence: 93%
“…Although recent research [14] concludes that LACE (which is the base for LACE+) could not accurate predict unplanned readmission, the presented system will include more data than LACE. One of the reasons is that in the available data there can be found a set of variables different from the ones used in LACE+ validation.…”
mentioning
confidence: 93%
“…Findings demonstrated that the LACE index [9] may be useful in the identification of patients at risk for readmission to hospitals in Asian countries. [10] A retrospective study of 253 patients was conducted to externally validate the accuracy of using the LACE index [9] to predict 30 day readmissions in patients experiencing congestive heart failure [11] (CHF) exacerbation. Wang et al [11] found that the LACE index [9] may be more useful in predicting the incidence of visits to the emergency department during the post discharge period.…”
Section: Introductionmentioning
confidence: 99%
“…[10] A retrospective study of 253 patients was conducted to externally validate the accuracy of using the LACE index [9] to predict 30 day readmissions in patients experiencing congestive heart failure [11] (CHF) exacerbation. Wang et al [11] found that the LACE index [9] may be more useful in predicting the incidence of visits to the emergency department during the post discharge period. The ability to provide patients with valuable community health resources during the post discharge period may reduce the number of visits to the emergency department by this population.…”
Section: Introductionmentioning
confidence: 99%
“…It calculates a score predictive of patient risk level based on length of stay (LOS), acuity of admission, medical comorbidities, and number of emergency visits in the 6 months leading up to admission [10]. The LACE index was first externally validated in congestive heart failure patients [10,11], and has also been validated in the general population of hospitalized patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…It calculates a score predictive of patient risk level based on length of stay (LOS), acuity of admission, medical comorbidities, and number of emergency visits in the 6 months leading up to admission [10]. The LACE index was first externally validated in congestive heart failure patients [10,11], and has also been validated in the general population of hospitalized patients [12]. Further, based on this scoring system, Bronstein et al [13] in a prospective, randomized fashion demonstrated that social work intervention for hospitalized patients based on a LACE score ≥ 7 decreased readmission likelihood by 22% compared to standard treatment.…”
Section: Introductionmentioning
confidence: 99%